Representing the Phlegm: the Portrait of the Phlegmatic in Cesare Ripa’s Iconology - Koźluk, Magdalena (Studia Ceranea, 2023)
This article is the second in a series of works which aims to contribute to documenting the success of the medical theory of individual complexions, derived from the theory of the four humours, through the major work which constitutes the Iconologia of the Italian humanist Cesare Ripa (1555–1622). We analysed here the figure of the phlegmatic and undertook to determine the reasons which governed the choice of the attributes retained by Ripa (portliness, pallor of the skin, coat in badger furs, tilted head and girded with a black headband, turtle) to offer poets, painters and sculptors the archetype of a character dominated by cold and damp phlegm. To this end, we have been interested in the medical and iconographic sources on which the author was able to rely and have tried to identify the attributes which are part of tradition and those which testify to an inuentio of the author in the iconographic art.